A comparative study on vietnamese and english telivision advertisements = Nghiên cứu so sánh giữa ngôn ngữ quảng cáo truyền hình Tiếng Anh và Tiếng Việt - Trần, Thái An (2021)
Nowadays, under the influence of the explosive growth of products and services production, business and enterprises are under great pressure of highly competitive business environment. Simultaneously, the development speed of mass media is significant. By the way, manufacturers and services providers make the most of mass media at the aim of competing with other opponents in terms of introducing and advertising their products and services to customers and clients. It can be clearly seen as